Identification barriers to entry in the sport tourism industry: A challenge for local sports entrepreneurs - Julianti P, Eva; Yusmawati; Widyaningsih, Heni; Mulyana; Halim, Abdul (Journal Sport Area, 2023)
The Indonesian sports industry is required by law to contribute to the country's gross domestic product (GDP) by becoming an upstream-to-downstream industry, which refers to the total value added to sports products annually and is a component of GDP. The objectives of this study were to find the factors that become barriers to entry (and also exit) from the sports industry. The study used a qualitative method. Using the purposive method, the data were collected from 10 people including the village head, entrepreneurs, and Cisaat Village Community through FGD’s (Forum Group Disscussion) and semi-structured interviews were gathered. To analyze the data using thematic analysis. Cisaat Village was chosen as an analysis material to find barriers to entry factors, especially for sport tourism. The findings of this study are that the capital factor, the lack of knowledge and experience, human resources, are the most barrier to entry in sport tourism industry. As implications of future research, researchers can use these factors to identify how they affect sports entrepreneurs in their countries. By addressing these barriers, the sports industry can thrive and make a substantial contribution to national economic development.